Penggunaan Permainan Bowling dalam Pengenalan Angka Terhadap Anak Usia Dini di RA Tadika Adnani - Samhani Siregar; Ali Masran Daulay; Hanifah Oktarina (Institut Nalanda, 2025)
Samhani Siregar. Nim (19030058). This thesis is about the Use of Bowling Game in the introduction of numbers to early childhood at RA Tadika Adnani with research objectives 1. How to use bowling games to improve number recognition for early childhood in RA Adnani Kindergarten research is included in qualitative descriptive research, data collection is carried out using observation methods, documentation. Data analysis is carried out after the data is collected using triagulation techniques (comparing, checking, checking the validity of the data) with the results of observation and documentation. The results of the analysis of the use of educational game tools using bowling games in the recognition of numbers for early childhood at RA Adnani Kindergarten have begun to develop as expected, the evaluation carried out by teachers provides reports on children's behavior and development to parents. This is very helpful for children in developing early childhood number bowling games that have been applied by teachers so that children are able to recognize numbers well and correctly. The indicators developed in the bowling game are that children are able to recognize numbers, children are able to pronounce numbers 0-9 clearly, children are able to match number symbols.